Pelatihan Pemasaran Digital untuk Memperkuat Entrepreneurial Self-Efficacy pada UMKM Pedesaan Air Naningan, Kabupaten Tanggamus, Lampung - Kumagaya, Johannes P.; Suyarti, Sri (Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital transformation creates opportunities for rural MSMEs in Air Naningan, Tanggamus Regency, Lampung; however, limited digital literacy and low self-confidence remain major challenges. This community service initiative aims to enhance entrepreneurial self-efficacy (ESE) and business performance through the integration of practice-based digital marketing training and structured mentoring. The method employed was a quasi-experimental one-group pre-test–post-test design involving 20 MSME actors over a four-month period, with interventions including workshops, mentoring, and self-efficacy reinforcement. The results indicate a significant increase in ESE from 2.34 to 3.89 (↑66.24%; p < 0.001; d = 3.10), along with an average income growth of 35%. These findings suggest that mastery experience and effective mentoring play a crucial role in strengthening self-confidence and encouraging digital adoption. Therefore, integrating technical training with psychological empowerment is a key strategy for empowering rural MSMEs.